Oat-cell carcinoma of the oesophagus: a recently recognized entity. - Cook, M G (1976)
A primary oat-cell carcinoma of the oesophagus is described with an adjacent squamous carcinoma, both parts having characteristic ultrastructure. The origin of this mixed tumour is discussed together with the literature on oesophageal carcinomas having an oat-cell pattern.